17O Hyperfine Spectroscopy Reveals Hydration Structure of Nitroxide Radicals in Aqueous Solutions. Issue 4 (15th December 2022) - Hecker, Fabian; Fries, Lisa; Hiller, Markus; Chiesa, Mario; Bennati, Marina
Abstract: The hydration structure of nitroxide radicals in aqueous solutions is elucidated by advanced 17 O hyperfine (hf) spectroscopy with support of quantum chemical calculations and MD simulations. A piperidine and a pyrrolidine‐based nitroxide radical are compared and show clear differences in the preferred directionality of H‐bond formation. We demonstrate that these scenarios are best represented in 17 O hf spectra, where in‐plane coordination over σ ${σ }$ ‐type H‐bonding leads to little spin density transfer on the water oxygen and small hf couplings, whereas π ${{\rm π }}$ ‐type perpendicular coordination generates much larger hf couplings. Quantitative analysis of the spectra based on MD simulations and DFT predicted hf parameters is consistent with a distribution of close solvating water molecules, in which directionality is influenced by subtle steric effects of the ring and the methyl group substituents. Abstract : The hydration structure of two different nitroxide radicals in bulk water is investigated by hyperfine spectroscopy that detects H2 17 O. Combination of ENDOR and HYSCORE methods reveals preferred coordination geometries and H‐bonding. Molecular dynamics simulations combined with DFT calculations provided the link between observed spectroscopic parameters and their distribution.